Model for Land Use Optimisation for Flood Management in Lasolo Watershed, Indonesia - Tasmadar, Tasmadar; Rianse, Usman; Kadir, Ishak; Sukri, Ahmad Syarif (Technium Social Sciences Journal, 2023)
Changes in land use from vegetation to non-vegetation in the Lasoso watershed contribute to an increase in the run-off coefficient caused by inundation during the wet season. Therefore, engineering is required to reduce discharge from surfaces. This study seeks to optimize land use in order to manage flooding. This study employs the paimin (modified) method with three different scenarios: Business as usual (BAU), simultaneous, and discrete. Results indicated that the BAU scenario has throughfall and retention capacity values of 15.55 percent and 19.39 percent of the total watershed area, respectively. scenario-2 (simultaneous) decreased throughfall and increased storage capacity (15.35 and 24.65%, respectively); scenario-3 (discrete) also improved. Comparing throughfall values reveals that the discrete simulation (-0.0020) is greater than the simultaneous scenario (-0.008), whereas the retention capacity has the same value (0.0020). The discrete simulation is superior to the simultaneous simulation in terms of optimizing its use for flood management in the Lasolo catchment.